Vesicoureteral Reflux, a Scarred kidney, and Minimal Proteinuria: An Unusual Cause of Adult Secondary Hypertension. (9th November 2011) - Sandal, Shaifali; Khanna, Apurv
Abstract : Hypertension affects about 65 million individuals in the United States. In adult patients, primary aldosteronism and renovascular causes are described as most prevalent. Vesicoureteral reflux as a cause of hypertension, while commonly described in pediatric populations, is less prevalent in the adult population especially in the absence of proteinuria. We present the case of a 31-year-old female presenting with early onset hypertension. Workup for renovascular hypertension was unrevealing. She was found to have right-sided vesicoureteral reflux with a unilateral scarred kidney. Patient underwent a nephrectomy with marked improvement in blood pressure control.